Laparoscopic Spigelian Hernia Repair - Barnes, T; McWhinnie, D (Lippincott, Williams & Wilkins, 2016)
Purpose: Spigelian hernias (SHs) account for 1% to 2% of abdominal wall hernias. Traditionally they have been repaired using an open technique. Since 1992, laparoscopic methods have become increasingly popular with various techniques being described in the literature. This systematic review aims to represent the current trends in laparoscopic repair of SHs. Materials and Methods: The databases MEDLINE and EMBASE were searched for appropriate terms regarding SH repair. Papers describing laparoscopic repair of SH were included. Results: Fifty articles were identified for the final review. No randomized controlled trials comparing laparoscopic techniques were identified. Two hundred thirty-seven SHs were repaired by various techniques. Intraperitoneal onlay mesh technique was the most popular repair method with minimal complications and recurrences reported in all techniques. Conclusions: There are a number of laparoscopic techniques available to the surgeon repairing a SH. Overall, laparoscopic repair of the SH is a safe and acceptable method.